2008
DOI: 10.1051/0004-6361:200811131
|View full text |Cite
|
Sign up to set email alerts
|

Eruption of magnetic flux ropes during flux emergence

Abstract: Aims. We investigate the formation of flux ropes in a flux emergence region and their rise into the outer atmosphere of the Sun. Methods. We perform 3D numerical experiments by solving the time-dependent and resistive MHD equations. Results. A sub-photospheric twisted flux tube rises from the solar interior and expands into the corona. A flux rope is formed within the expanding field, due to shearing and reconnection of field lines at low atmospheric heights. If the tube emerges into a non-magnetized atmospher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
174
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(194 citation statements)
references
References 23 publications
17
174
0
3
Order By: Relevance
“…The studied filament in this paper was existing for several rotations. MHD models show that the convection cells are different in flux emergence regions (Archontis & Török 2008;Archontis & Hood 2009). Future studies of the coupling between convection and filaments should be done during filament emergence.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…The studied filament in this paper was existing for several rotations. MHD models show that the convection cells are different in flux emergence regions (Archontis & Török 2008;Archontis & Hood 2009). Future studies of the coupling between convection and filaments should be done during filament emergence.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Therefore is remains unclear whether such a process may occur. In contrast, many authors have shown that during the process of flux emergence, after the top of the flux rope has emerged, magnetic reconnection or helicity injection (Manchester et al, 2004;Magara, 2006;Archontis and Török, 2008;Fan, 2009) may reconfigure the emerged coronal arcade to produce a secondary coronal flux rope. During the formation of the secondary flux rope the reconnection may then lift cool dense material to coronal heights.…”
Section: Active Region Filamentsmentioning
confidence: 97%
“…A key feature in these experiments is the formation of a new flux rope at photospheric/chromospheric heights (Magara & Longcope 2001;Manchester et al 2004;Gibson & Fan 2006;Archontis & Hood 2008), consisting of weakly twisted magnetic field lines surrounding its axis (Archontis & Török 2008;Archontis & Hood 2010). The axis of the new flux rope is distinct from the axis of the original subphotospheric flux tube that initially emerges from the solar interior.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the magnetic field after the break-up of the original flux tube into two parts could be considered as "partial-emergence" of the magnetic field (e.g. Manchester et al 2004;Gibson & Fan 2006;MacTaggart & Hood 2009;Archontis & Török 2008). Indeed, the exact location of the internal reconnection with respect to the original axis of the emerging field determines whether all, some (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation